Mulheres do Araripe: trajetórias de lutas e representatividade política (1982-2004) - Carvalho, Maria José Lopes de (2011)
The research WOMEN FROM ARARIPE: Struggle paths and political representation (1982-2004) seeks to discuss, ponder and turn into history, based on the relation between history and gender, the role of these women from the Araripe Mountains region, especially from the cities of Araripina-PE and Simões-PI. In Women from Araripe one searches to analyze the political and party engagement from women as social and historical beens looking for elective positions or as part of the election process. This paper‟s greatest objective is to go over the insertion (participation) and involvement process of women in the political arena of both cities here in debate during the period of 1982 to 2004. The second most pertinent goal of this research is the identification of the different ways and strategies used by women candidates when seeking votes in electoral times. At the end, what one hopes to attain by this paper is to understand the struggle paths of the women from Araripe when exercising their participation and political intervention in the electoral processes and at politically decisive public institutions, throughout history